Merubah Ancaman Bahaya Limbah Cair Industri Tahu Menjadi Peluang Ekonomi - Maharso Maharso; Darmiah Darmiah; Zulfikar Ali As (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2014)
Abstrak : Changing the Threat of tofu Wastewater Hazardous to be Economical Oppurtunities. Wastewater from Tahu industry known as “whey” are offensive and be able to cause negative impact to the environment. This problem is caused by the characteristic of whey which is hot, acid, and containing much organic material. Because of this characteristic, their dissolve oxygen is also zero ppm. Measurement of tahu and tempe wastewater in Semanan, Jakarta Barat showed that the whey contains 1.324 mg/l of BOD5, 6.698 mg/l of COD, 84,4 mg/l of NH4, 1,76 mg/l of nitrate and 0,17 mg/l of nitrite 1). The potential hazard of whey to aquatic life can be measured by counting the concentration of whey’s parameter which be able to cause the death of tilapia (LC50), that is from 3,80% up to 11,5% at 24 hours exposure; 3,67% up to 14,30% at 72 hours exposure; and 3,38% up to 12,10% at 72 hours exposure 2). On the other hand, Acetobacter can change sugar to be vinegar, with byproduct is film coat “nata” floating. Factors influencing Acetobacter growth are sources of Carbon and Nitrogen. Appropriate nutrient content will produce “rendemen nata” (de coco) maximum, that is up to 93,3% 3). This study aims to know does the whey which is added by Acetobacter xylinum can produce nata de soya?. The result gave information that if into the whey added the Acetobacter (made from ripe pineapple) as a starter, and urea in acidic condition, would produce rendemen nata approximately 30%–40%. 4). Keywords: wastewater of tahu industry; nata de soya of whey